2017
DOI: 10.22211/cejem/68391
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Application of Stabilized-Ni/Fe Bimetallic Nanoparticles for the Selective Elimination of Chlorate Impurity in Military Grade Ammonium Perchlorate

Abstract: Ammonium perchlorate (AP) is used as the most common oxidizer in composite solid propellants. Control of chlorate impurity in military grade ammonium perchlorate is important, since it has an undesirable effect on the thermal decomposition of ammonium perchlorate. In this work stabilized Ni/Fe bimetallic nanoparticles (S-Ni/Fe NPs) were synthesized using the borohydride reduction method (BRM) in the presence of starch as a stabilizing agent, and they were characterized by field emission scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…and Mikami et al . 37 , 38 . On the basis of the data obtained, it was concluded that the CuO sample was characterized by high homogeneity (PdI = 0.089) and that the particle size of the analyzed product was in the range 24–79 nm (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…and Mikami et al . 37 , 38 . On the basis of the data obtained, it was concluded that the CuO sample was characterized by high homogeneity (PdI = 0.089) and that the particle size of the analyzed product was in the range 24–79 nm (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This could be a reason for the observed slower kinetics under Electro-Peroxide treatment of MNT. Under Electro-Fenton conditions, these intermediates form complexes with ferric salt and regenerate ferrous ion which results in higher concentration of OH radicals through fast Electro-Fenton reaction as mentioned in equation ( 5) and (6). As a result of this, MNT concentration decreases at a faster rate under Electro-Fenton reaction.…”
Section: Probable Reaction Mechanism During Mnt Degradation Under Electro-fenton Reactionmentioning
confidence: 97%
“…Carbon column is used for the removal of toxic chemicals from the waste water 4 and carboxymethyl chistosan intercalated montmorikonite (CMCTS-MMT) clay is also used as adsorbent for the removal of cationic dye from the waste water. 5 Recently a method has been developed for the treatment of the energetic compounds contaminated waste water using zero-valent iron nanoparticles (ZVINs) 6 , Photo-Fenton process 7 and Photo-oxidation methods 8 are currently gaining much interest but involve use of UV light which is hazardous to eyes and skin etc. and also consumes high electrical energy.…”
Section: Introductionmentioning
confidence: 99%